2016
DOI: 10.5713/ajas.16.0591
|View full text |Cite
|
Sign up to set email alerts
|

Influences of somatic donor cell sex on in vitro and in vivo embryo development following somatic cell nuclear transfer in pigs

Abstract: ObjectiveThe present study investigates pre- and post-implantation developmental competence of nuclear-transferred porcine embryos derived from male and female fetal fibroblasts.MethodsMale and female fetal fibroblasts were transferred to in vitro-matured enucleated oocytes and in vitro and in vivo developmental competence of reconstructed embryos was investigated. And, a total of 6,789 female fibroblast nuclear-transferred embryos were surgically transferred into 41 surrogate gilts and 4,746 male fibroblast n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several studies found that donor cell source, passage number, gender, and differentiation status influence SCNT efficiency (Li et al, ; Powell et al, ; Wakayama, Perry, Zuccotti, Johnson, & Yanagimachi, ; Yoo et al, ). For example, pluripotent and undifferentiated donor cells, which possess a loose nuclear chromosome structure, have proven easier to reprogram, suggesting that complete nuclear reprogramming following nuclear transfer is more likely when the genome is easily accessible (Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that donor cell source, passage number, gender, and differentiation status influence SCNT efficiency (Li et al, ; Powell et al, ; Wakayama, Perry, Zuccotti, Johnson, & Yanagimachi, ; Yoo et al, ). For example, pluripotent and undifferentiated donor cells, which possess a loose nuclear chromosome structure, have proven easier to reprogram, suggesting that complete nuclear reprogramming following nuclear transfer is more likely when the genome is easily accessible (Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reprogramming varies with the type of donor nucleus (Kato & Tsunoda, ). Studies demonstrated that the developmental competence of cloned embryos was not significantly different between the sexes (Sandhu et al., ; Yoo et al., ). However, Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reprogramming varies with the type of donor nucleus (Kato & Tsunoda, 2010). Studies demonstrated that the developmental competence of cloned embryos was not significantly different between the sexes (Sandhu et al, 2016;Yoo et al, 2016). However, Liu et al reported that the donor cells' sex had significant effects on nuclear transfer efficiency of cloned goats (Liu et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Park et al Effects of the surrogate mother in pig SCNT species, and the production of transgenic animals for therapeutic applications. Pig SCNT has also been studied with the aim of improving the efficiency of production (Betthauser et al, 2000;Huang et al, 2000;Onishi et al, 2000;Polejaeva et al, 2000;Li et al, 2013;Rim et al, 2013;Callesen et al, 2014;Huan et al, 2015;Yoo et al, 2017;Jeong et al, 2020).…”
mentioning
confidence: 99%
“…Given the low efficiency of SCNT, many questions on the mechanisms involved remain unanswered in both basic and applied fields. The difficulty in porcine cloning has been attributed to multiple factors, including oocyte quality (in vivo matured vs. in vitro matured), donor cell type, inadequacies in the culture and media used during the micromanipulation process, lack of an efficient activation method, requirement for a minimum number of fetuses, and the appropriate recipient conditions to maintain a pregnancy (Bang et al, 2002;Yoo et al, 2017;Dang-Nguyen et al, 2020). Polejaeva et al (2000) reported the first successful birth of five healthy cloned female piglets by SCNT using in vivo-matured oocytes.…”
mentioning
confidence: 99%